Optimasi Pengurutan Data Bilangan dengan Menggabungkan Algoritma Selection Sort Hybrid dan Bucket Sort - Risqi Pradana Aryanto; Agung Nilogiri; Ari Eko Wardoyo (Jurnal Pendidikan Informatika (EDUMATIC), 2023)
Sorting algorithms are crucial in data processing, particularly for integer data. However, as the number of integers to be sorted increases, the sorting algorithm takes longer to complete, especially for algorithms with O(n2) complexity. This article discusses optimizing integer data sorting by combining the Selection Sort Hybrid and Bucket Sort algorithms. The study aims to test the performance of the Selection Sort Hybrid and Bucket Sort algorithms and compare them with other data sorting algorithms. The research method used is experimental quantitative research, using randomly generated data using Python. The data were tested using the Combined Selection Sort Hybrid with Bucket Sort algorithm, Selection Sort Hybrid, Quick Sort, and Merge Sort. Data analysis was done by calculating the execution time of each sorting algorithm. The results show that the Selection Sort Hybrid and Bucket Sort algorithms are faster than other sorting algorithms in testing with large and complex integer data. Therefore, combining Selection Sort Hybrid and Bucket Sort algorithms can improve the efficiency and speed of sorting complex integer data.